IMPLICATION OF THE USE OF REFERENCE USED BY K-POP FANS IN INSTAGRAM AND X - Soedjarwo, Gabriella Novianty; Retnoningsih, Emerentiana Ivana (Sanata Dharma University, 2025)
The K-pop industry has reached its peak. The influence of K-pop has been everywhere. Even in Korea itself, the K-pop industry has gained popularity among businessmen and youngsters who want to enter the K-pop industry. K-pop songs are also famous around the world. The fame of the song goes hand in hand with the fame of the singer. The singer, usually called an idol, has fandoms in other countries. The idols receive adoration from the fans by giving gifts, buying the album, and even defending the idols if they are “attacked” by another fandom. This kind of behaviour has resulted in the fans having a sort of behavioural disorder so-called celebrity worship syndrome. This study aims to reveal how the use of references by fans reveals their psychological state towards the idol. The data was taken from the comment session of the news about K-pop idols on Instagram and X. There were 100 data to be analysed. This research found that there are nine references used: pacar/ayank, sayang/love/cinta, oppa, suami/istri, king, prince/pangeran, my lord/ tuan, legend, and my life. Those references were analysed using the theory semantics to see the correlation between the choice of reference with the world the K-pop fans think they are in. The conclusion is that the fans see their idol as someone having an intimate relationship with them, and the fans also see the idols as someone they adore highly.